2016
DOI: 10.1007/s11661-016-3573-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Grain Growth and Grain Refinement in Bulk Ultrafine-Grained Copper under Tensile Deformation at Room Temperature

Abstract: Grain growth and grain refinement behavior during deformation determine the strength and ductility of ultrafine-grained materials. We used asymmetric cryorolling to fabricate ultrafine-grained copper sheets with an average grain width of 230 nm and having a laminate structure. The sheets show a high-true failure strain of 1.5. Observation of the microstructure at the fracture surface reveals that ultrafine laminate-structured grains were simultaneously transformed into both equiaxed nanograins and coarse grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Shi et al [17] found that dislocations in some special configurations are movable, which prevents localized shear deformation and contributes to the improved ductility of CR-processed Zr. Recently, Yu et al [18] found that simultaneous grain growth and grain refinement appear in CR-processed UFG Cu sheets, which results in a high-true failure strain of 1.5. A number of studies on CR-processed UFG Al have reported good ductility of the materials [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [17] found that dislocations in some special configurations are movable, which prevents localized shear deformation and contributes to the improved ductility of CR-processed Zr. Recently, Yu et al [18] found that simultaneous grain growth and grain refinement appear in CR-processed UFG Cu sheets, which results in a high-true failure strain of 1.5. A number of studies on CR-processed UFG Al have reported good ductility of the materials [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Ten diffnrnncn in mnceanical propnrtins rnsults in a snvnrn senar dnformation in ten surfacn laynrs, and tenn ten grains arn rnfinnd grnatly. Dun to ten supprnssion of ten dynamic rncovnry bneavior at cryognnic tnmpnraturn, comparnd wite room-tnmpnraturn roll bonding, cryorolling is morn conducivn to grain rnfinnmnnt [32][33][34][35][36][37], as illustratnd in Fig. 8(b) and (d).…”
Section: ) Interface Bondingmentioning
confidence: 99%
“…Ten UFG/NGs nnar ten intnrfacn grow undnr senar strnss. Tenrn arn many rnports teat UFG/NG grow during room-tnmpnraturn dnformation [32,48,49]. uiao nt al [49] rnportnd teat ten grains grow from 30±7.5 nm to 129±43nm in nlnctro-dnpositnd NG Ni during eige-prnssurn torsion.…”
Section: ) Interface Bondingmentioning
confidence: 99%
“…The mechanical properties of laminate composites can be optimized through optimization of intermetallic layer and grain size . In addition, cryorolling is an efficient way to fabricate the ultrafine grain materials such as Cu, Al, and Ti . However, there are few reports on the enhanced mechanical properties of sandwich‐like composites by cryorolling.…”
Section: Introductionmentioning
confidence: 99%